Development of a questionnaire to assess dietary restrictions runners use to mitigate gastrointestinal symptoms - Jill A. Parnell; Hailey Lafave; Kim Wagner-Jones; Robyn F. Madden; Kelly Anne Erdman (Taylor & Francis Group, 2019)
Background Exercise induced gastrointestinal (GI) symptoms can plague athletes, especially runners. Sport nutrition recommendations are nutrient rather than foods focused and do not adequately address strategies to reduce GI symptoms. The objective was to develop a valid and reliable questionnaire to evaluate pre-training and pre-racing voluntary food restrictions/choices, reasons for avoiding foods, and gastrointestinal symptoms in endurance runners. Methods Validity testing occurred through four Registered Dietitians, three of whom possess Master's degrees, and a dietetic trainee who provided initial feedback. Additionally, one Registered Dietitian is a Board Certified Specialist in Sports Dietetics (CSSD), and another has an International Olympic Committee Diploma in Sports Nutrition. The second version was sent out to nine different experts who rated each question using a Likert scale and provided additional comments. For reliability testing, the questionnaire was administered to 39 participants in a test re-test format. Kappa statistics and the prevalence-adjusted bias-adjusted kappa (PABAK) were used to assess the reliability. Results All questions had an average Likert scale rating of 4/5 or greater. All test re-test results falling under basic information exhibited substantial agreement (kappa ≥0.61). All medical questions including food allergies and intolerances had moderate (kappa ≥0.41) or higher agreement. Responses were less consistent for food avoidances while training (5/28 outcomes) versus racing (0/28 outcomes) with a kappa below 0.41. All reasons for avoiding foods were deemed reliable. Regarding symptoms, side stitch while training and gas while racing were the only flagged categories. Conclusions Overall, the questionnaire is a valid and reliable tool to evaluate voluntary dietary restrictions among endurance runners. Future studies can use the questionnaire to assess dietary strategies runners employ to reduce GI distress and optimize performance.